Becoming abject: testing the limits and borders of reading mediation. Issue 1 (2nd January 2022) - Véliz, Soledad; García-González, Macarena
ABSTRACT: Reading mediation is a concept used in Latin America and Spain, referring to the nurturing role played by adults in forging relationships between children and books. In this article, we conceptualize reading mediation as a 'technology of affect'. We propose 'mediation-as-usual', a normative becoming of this technology, tasked with producing categories and identities regarding readers. Within this technology, adults are produced as empathetic, caring, and providers of safe spaces for reading. We report on literary encounters at a school in Santiago, Chile, with a 'challenging' picturebook. We were involved in the emergence of what we term 'abject mediation', a figuration that produces the limits and boundaries of mediation-as-usual, and, we argue, has transformative potential. However, this is an ephemeral figuration, as reterritorialization works to assimilate the border elements, actualizing mediation-as-usual. We discuss how these figurations may help to question normative ways of producing readers.